2018
DOI: 10.3390/catal8060239
|View full text |Cite
|
Sign up to set email alerts
|

A Novel High-Activity Zn-Co Catalyst for Acetylene Acetoxylation

Abstract: In this paper, Zn(OAc) 2 /AC and Zn-Co/AC catalysts were prepared and applied in an acetylene acetoxylation reaction. Compared with monometallic Zn(OAc) 2 /AC catalyst, which is widely applied in industry, the Zn-Co catalysts exhibited excellent catalytic performance. Transmission electron microscopy results displayed that the addition of cobalt improved the dispersity of zinc acetate particles and inhibited catalyst sintering on the catalyst surface. X-ray photoelectron spectra suggested that the Co additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These results revealed that the existence of a dicarboxylic system reduced the adsorption strength of C 2 H 2 on the catalysts, and this corresponded to the TPD results ( Figure 7 a). Additionally, to correlate the actual experimental process to the possible mechanism [ 8 , 9 , 11 ], a hypothetical model was developed for the adsorption of acetylene during the reaction. As shown in Figure 9 (a 1 ), a molecule of CH 3 COOH was first adsorbed on the monocarboxylic catalyst to form a complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results revealed that the existence of a dicarboxylic system reduced the adsorption strength of C 2 H 2 on the catalysts, and this corresponded to the TPD results ( Figure 7 a). Additionally, to correlate the actual experimental process to the possible mechanism [ 8 , 9 , 11 ], a hypothetical model was developed for the adsorption of acetylene during the reaction. As shown in Figure 9 (a 1 ), a molecule of CH 3 COOH was first adsorbed on the monocarboxylic catalyst to form a complex.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this mechanism, the rate-limiting step is the adsorption of acetylene [ 6 ]. Some scholars [ 7 , 8 , 9 ] have demonstrated that the adsorption strength and capacity of acetylene significantly influences the acetylene acetoxylation reaction. Thus, the regulation of the adsorption of acetylene must be considered in the field of catalysis science.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A type of catalyst containing nitrogen with high activity was prepared by Yu et al [20]. Wang and coworkers [21,22] used zinc-cobalt and zinc-nickel as active components and explained the relevant reaction mechanisms. Wang et al [23] prepared nitrogen-doped AC by modifying AC with dicyandiamide (N-AC) and used it for loading Zn(OAc) 2 , which exhibited good performance.…”
Section: Introductionmentioning
confidence: 99%